Quality improvement project aimed at improving the reliability of spontaneous awakening trials in a district general intensive care unit. Issue 2 (24th May 2019) - Ferraioli, Donna; Ferguson, Laura; Carberry, Martin
Abstract : Traditionally regarded as good practice, continuous infusions of sedation and analgesic medications are used to reduce anxiety and distress and facilitate care of mechanically ventilated patients in the intensive care unit (ICU). Growing evidence has demonstrated that use of such infusions prolongs days spent invasively ventilated, increases the incidence of ICU acquired weakness and delirium and subsequently increasing the duration of their ICU and hospital stay. Several critical care guidelines recommend titrating to light sedation ±a daily sedation hold or spontaneous awakening trial (SAT). Given the known beneficial effects of sedation holds, we aimed to increase their use within our ICU, a 10-bedded unit with mixed ICU and high-ependency unit facilities in National Health Service Scotland. A retrospective case note review was performed to obtain baseline data of SAT eligible patients who received a sedation hold. The model for improvement 1 was used to implement an ICU protocol based on the 'Wake up and breath' guidelines 2 and measure the improvements made. The median percentage of SAT eligible patients that received a sedation hold increased from 47% to 96% during the project period. No significant adverse events were reported during this period and a reduction in ventilation and unit stay was observed. Quality improvement methods have facilitated successful and safe integration of a daily sedation hold protocol in our ICU.